СЛАВЯН ТІЛДЕРІНДЕГІ ТҮРКИЗМДЕРДІҢ ЗЕРТТЕЛУ ТАРИХЫ - Алжанбаева, Ұ. Т. (Journal of Oriental Studies, 2016)
В этой статье рассматривается вопросы изучениятюркизмов в славянских языках, пути проникновения,проблемы взаимовлияния и взаимообогащения контак-тирования языков.In this article it is considered studying questions ofTurkic words in slavic languages, a way of penetration, aproblem of mutual influence and mutual enrichment ofengagement of languages.